Analysis of Clinical Profile, Investigation, and Management of Ocular Cysticercosis Seen at a Tertiary Referral Centre. (19th May 2018) - Ganesh, Sudha K.; Priyanka,
ABSTRACT: Aim : To analyze the demographic profile, clinical presentation, diagnosis, management, and outcome of ocular cysticercosis (OC) seen at a tertiary referral center. Design : Retrospective case series. Material and methods : Records of patients with diagnosis of OC from January 2000 to September 2015 were retrieved and the data was analyzed. Results : 102 eyes of OC were seen. 72(71%) eyes had extraocular cysticercosis (EC) and 30(29%) eyes had intraocular cysticercosis (IC). EC was located in the orbit in 69/72 (96%) eyes. Symptoms of extraocular cysticercosis were restriction of ocular movement in 33 eyes (46%). IC was located in vitreous 17 eyes (57%). Symptom of IC was drop in vision in 26/30 eyes (87%). EC was managed medically with albendazole and steroid. Surgical excision was done for IC. Conclusion : EC was more common than IC. Prompt and appropriate management of OC results in good visual outcome.